Entry and Learning - Devinney, Timothy M. (Management Science, 1987)
This paper shows the difficulties associated with discerning the impact of learning and pressures of competitive entry on the price and cost of production in commodity markets. It shows that the patterns of price and cost movements over time will be dramatically affected by the entry of new competitors. If firms possess U-shaped average cost curves, entry alone can generate price and cost declines which look like learning induced reductions. Alternatively, cost increases may occur even when learning is quite strong. This research has dramatic managerial and empirical implications. Managers, operating in highly competitive environments subject to rapid entry, must put more emphasis on the role of their own day-to-day decisions in affecting cost. The fact that costs have declined may have nothing to do with learning but may be driven by their reactions to competitive pressures. Investigators empirically estimating learning curves must also be cognizant of the role entry plays in affecting cost. Simple comparisons of cost or price versus accumulated production, so common in applied studies, seriously confounds the role of entry and the consequent managerial decisions in determining accumulated production. It is argued that a more careful examination of entry needs to be taken into account when evaluating the role of learning and the estimating cost curves.